Presenilins and mitochondria—an intriguing link: mini-review - Makarov, Mark; Kushnireva, Liliia; Papa, Michele; Korkotian, Eduard (Frontiers in Neuroscience, 2023)
This review uncovers the intricate relationship between presenilins, calcium, and mitochondria in the context of Alzheimer’s disease (AD), with a particular focus on the involvement of presenilin mutations in mitochondrial dysfunction. So far, it is unclear whether the impairment of mitochondrial function arises primarily from damage inflicted by β-amyloid upon mitochondria or from the disruption of calcium homeostasis due to presenilins dysfunctions. The roles of presenilins in mitophagy, autophagy, mitochondrial dynamics, and many other functions, non-γ-secretase related, also require close attention in future research. Resolution of contradictions in understanding of presenilins cellular functions are needed for new effective therapeutic strategies for AD.